Parasitic Weeds Biology and Control - Dor, Evgenia; Goldwasser, Yaakov (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The parasitic lifestyle in plants has always been the subject of curiosity of scientists, but during the last decade, our understanding of parasitic plant-host interactions has greatly evolved due to rapid advances in molecular and genomic tools, especially high throughput DNA sequencing, transcriptomics, and metabolomics. Recent findings taken the science of parasitic plants to a higher level, opening up new horizons in parasitic weed management. The discovery of a novel family of phytohormones, the strigolactones, and their involvement in the host detection and evolution of parasitic plants, the detection of information exchange between host and parasite, and elucidation of the suppression of host defense mechanisms by parasites has led to a deeper understanding of physiological processes in host-parasite interactions. In the light of recent achievements, the re-evaluation of control management, including smart chemical control, crop breeding, and molecular genetics, are on the agenda.